Contextualização do ensino de matrizes como ferramenta motivadora - Mesquita, Newton Barros (2017)
The presented study however it had as objective generality to stand out the importance of the job of the tools of remote sensing and digital processing of images in the process of teach-learning of matrices with the job of MatLab software. One is about a study of bibliographical matrix (whose given they had been extracted of books, published scientific articles in the Internet, monographs, theses, dissertations and electronic small farms that bring information regarding the subject in quarrel), which was in search of reply for the following guiding question: Which the importance of the job of the tools of remote sensing and digital processing of images in the process of teach-learning of matrices with the job of MatLab software? To the end of you analyze them bibliographical accomplished was possible to perceive that the learning tend if to distance of the teach-learning process that not to wake up we ourselves the taste for the learning of the boarded subjects in classrooms for the professors. Ahead of this reality, the carried through studies signal that the job of the tools mentioned above is of excellent importance when of the calculation of matrices, since it tends to awake in the pupil the taste for the learning process, therefore does not move away it from the technologies of the information.